Benefits of step-by-step debulking microwave ablation for huge unresectable hepatocellular carcinoma patients after transcatheter arterial chemoembolization refractoriness. (31st December 2022) - Huang, Tao; Qi, Han; Shen, Lujun; Wu, Ying; Song, Ze; Cao, Fei; Liu, Yin; Xie, Lin; Chen, Shuanggang; Tang, Tian; Li, Hailiang; Zhang, Yanfang; et al.
Abstract: Objectives: To compare the safety and efficacy of step-by-step debulking Microwave Ablation (MWA) with Transarterial Chemoembolization (TACE) monotherapy for huge (≥10 cm in diameter) unresectable hepatocellular carcinoma (HCC) after TACE refractoriness. Methods: This is a multi-center retrospective study carried out on 599 patients with huge unresectable HCC who received TACE as first-line therapy at five hospitals from January 2009 to December 2018. A total of 103 patients with TACE refractoriness were divided into two cohorts: monthly step-by-step debulking MWA ( n = 52) or continued TACE ( n = 51). Overall survival (OS) and progression-free survival (PFS) after refractory TACE were evaluated. Residual liver and tumor volume were recorded for the MWA group. Results: Median follow-up period was 24.3 months and median OS and PFS were significantly longer in the MWA group than in the TACE group (OS 21.0 vs. 11.7 months, PFS 6.1 vs. 3.0 months, both p < 0.001). The one-, two-, and three-year OS rates in the MWA and TACE groups were 73.1%, 46.6%, and 37.2% versus 43.1%, 15.5%, and 2.9%, respectively. Furthermore, the 0.5-, 1-, and 2-year PFS rates in the MWA and TACE groups were 51.9%, 36.5%, and 25.0% versus 27.5%, 11.8%, and 0, respectively. Multivariate analyses confirmed that switching to debulking MWA treatment was an independent favorable prognostic factor for PFS and OS. In the MWA group, the average additions of residual liver volume/total liver volume were 7.7% ± 6.7%, 7.2% ± 10.2%, and 10.1% ± 8.8% after the first, second, and third MWA procedure. Conclusion: Step-by-step debulking MWA can significantly improve long-term OS and PFS in patients with huge unresectable HCCs compared with repeated TACE after TACE refractoriness. Key Point: The debulking MWA therapy provides significantly longer OS and PFS than continued TACE for patients with huge unresectable HCCs after TACE-refractory, especially with complete tumor ablation. The most common complications were fever (48.1%) and pain (46.2%) in the MWA group. Two major complications (abdominal infection) were recorded in the MWA group, which recovered after symptomatic treatment. During the course of repeated MWAs, liver hyperplasia appeared mainly after the second MWA procedure and the average maximum increased RLV/TLV rate was 16.3%±12.7%.